Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan (Literature Review Manajemen Sumber Daya Manusia - Cayla Salsa Raya; Dewi Sri Woelandari Pantjolo Giningroem; Dhea Puspita Sari; Muhammad Rafly (STIKes Ibnu Sina Ajibarang, 2024)
The Influence of Leadership Style and Organizational Culture is an article which is a review of literature in the field of knowledge. The aim of this article is to provide an understanding of the relationship between two types of organizational culture and employee working conditions. For the purpose of developing hypotheses and variables between roles that will be used in research that will be carried out in the future, within the scope of Human Resource Management knowledge. The article writing method is a research method that is based on information obtained from online sources such as Google Scholar, Mendeley, and other online academic sources. This is a qualitative descriptive analysis. The results of this article are as follows: : 1) ; Leadership style has a significant effect on employee performance 2. Organizational culture has a significant effect on employee performance 3) ; Leadership Style and Organizational Culture have a significant effect on employee performance.